Flows and Practices - Mehta, Lyla (Weaver Press, 2017)
For the past two decades, Integrated Water Resources Management (IWRM) has been the dominant paradigm in water resources. This book explores how ideas of IWRM are being translated and adapted in Mozambique, South Africa, Tanzania, Uganda and Zimbabwe. Grounded in social science theory and research, it highlights the importance of politics, history and culture in shaping water management practices and reform, and demonstrates how Africa has clearly been a laboratory for IWRM. While a new cadre of professionals made IWRM their mission, we show that poor women and men may not have always benefitted. In some cases IWRM has also offered a distraction from more critical issues such as water and land grabs, privatisation, the negative impacts of water permits, and a range of institutional ambiguities that prevent water allocations to small and poor water users. By critically examining the interpretations and challenges of IWRM, the book contributes to improving water policies and practices and making them more locally appropriate in Africa and beyond.